2012
DOI: 10.1016/j.ijggc.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Induced seismicity within geological carbon sequestration projects: Maximum earthquake magnitude and leakage potential from undetected faults

Abstract: a b s t r a c tWith developing countries strongly relying on fossil fuels for energy generation, geological carbon sequestration (GCS) is seen as a candidate for large reductions in CO 2 emissions during the next several decades. GCS does, however, raise some safety concerns. Specifically, it has been associated with induced seismicity, as a result of pressure buildup arising from prolonged CO 2 injection in GCS projects. This seismicity is a delicate issue for two main reasons. First, over a short time scale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(91 citation statements)
references
References 51 publications
0
89
1
1
Order By: Relevance
“…Numerical simulations have shown that CO 2 injection in closed reservoirs without a proper control of overpressure, i.e., allowing overpressure to exceed the maximum sustainable injection pressure, has the potential of triggering earthquakes of up to magnitude 4.5 in critically stressed faults (86). However, the magnitude of the simulated induced earthquakes becomes smaller than 3 when considering more realistic stress fields for sedimentary formations, with shear displacements of up to 6 cm (86,87). These numerical studies highlight the importance of overpressure management for avoiding felt induced seismicity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulations have shown that CO 2 injection in closed reservoirs without a proper control of overpressure, i.e., allowing overpressure to exceed the maximum sustainable injection pressure, has the potential of triggering earthquakes of up to magnitude 4.5 in critically stressed faults (86). However, the magnitude of the simulated induced earthquakes becomes smaller than 3 when considering more realistic stress fields for sedimentary formations, with shear displacements of up to 6 cm (86,87). These numerical studies highlight the importance of overpressure management for avoiding felt induced seismicity.…”
Section: Discussionmentioning
confidence: 99%
“…The adopted modeling approach has also been extensively applied for modeling fault activation associated with underground CO 2 injection (e.g. Cappa and Rutqvist, 2012;Mazzoldi et al, 2012;.…”
Section: Model Setupmentioning
confidence: 99%
“…2011), TOUGH-FLAC was expanded to applications, including geomechanical aspects of CO 2 sequestration and fault activation, geomechanical effects in gas production from hydrate bearing sediments, and geothermal energy production. Since 2011, TOUGH-FLAC applications have been further broadened along with an increasing number of users, including continued modeling of geomechanical aspects of CO 2 sequestration (Cappa and Mazzoldi et al, 2012;Rinaldi and Rutqvist, 2013;Jeanne et al, 2014a;Konstantinovskaya et al, 2014;Rinaldi et al, 2014aRinaldi et al, , b, 2015aFigueiredo et al, 2015), nuclear waste disposal , enhanced geothermal systems (Jeanne et al, 2014b(Jeanne et al, -d, 2015aRutqvist et al, 2015a;Rinaldi et al, 2015b), underground gas storage and compressed air energy storage 2015), and gas production from hydrate bearing formations ).…”
Section: Tough-flacmentioning
confidence: 99%